A Primer for the Exercise and Nutrition Sciences Thermodynamics, Bioenergetics, Metabolism - Scott, Christopher B. (Humana Press : Imprint: Humana, 2008)
The subject of thermodynamics is rarely found in Nutrition and Exercise Physiology textbooks. Yet this material is fundamental to any serious inquisition concerning energy exchange. This book provides a fresh approach to the study of energy expenditure by introducing the latest concepts in open system thermodynamics and cellular to whole-body energy exchange. A journey is undertaken by the reader, beginning with what energy is and where the energy in glucose is found, and ending with the concept of high versus low intensity exercise in augmenting weight loss. The text traces biological energy exchange, from the molecules in the food we eat to the energy demands of rest, physical exertion and its recovery. Because of life's continuous need for exchanges to take place with the environment, metabolism is proposed to be as much an act of engineering as it is biochemistry. The carefully researched text advances traditional exercise physiology concepts by incorporating contemporary thermodynamic and cellular physiology principles into the context of a 'working' metabolism. This book is written for upper level undergraduate and graduate students, but will also appeal to exercise physiologists, registered dieticians and nutritionists, and applies to cardiac rehabilitation, exercise science and health fitness programs.